Uridine‐cytidine kinase 2 (UCK2): A potential diagnostic and prognostic biomarker for lung cancer. Issue 9 (23rd August 2019) - Wu, Yingjie; Jamal, Muhammad; Xie, Tian; Sun, Jiaxing; Song, Tianbao; Yin, Qian; Li, Jingyuan; Pan, Shan; Zeng, Xingruo; Xie, Songping; Zhang, Qiuping
Abstract: Lung cancer has the highest morbidity and mortality among all cancers. Discovery of early diagnostic and prognostic biomarkers of lung cancer can greatly facilitate the survival rate and reduce its mortality. In our study, by analyzing Gene Expression Omnibus and Oncomine databases, we found a novel potential oncogene uridine‐cytidine kinase 2 ( UCK2 ), which was overexpressed in lung tumor tissues compared to adjacent nontumor tissues or normal lung. Then we confirmed this finding in clinical samples. Specifically, UCK2 was identified as highly expressed in stage IA lung cancer with a high diagnostic accuracy (area under the receiver operating characteristic curve > 0.9). We also found that high UCK2 expression was related to poorer clinicopathological features, such as higher T stage and N stage and higher probability of early recurrence. Furthermore, we found that patients with high UCK2 expression had poorer first progression survival and overall survival than patients with low UCK2 expression. Univariate and multivariate Cox regression analyses showed that UCK2 was an independent risk factor related with worse DFS and OS. By gene set enrichment analysis, tumor‐associated biological processes and signaling pathways were enriched in the UCK2 overexpression group, which indicated that UCK2 might play a vital role in lung cancer. Furthermore, in cytology experiments, we found that knockdown of UCK2 could suppress the proliferation and migration of lung cancer cells. In conclusion, our study indicated that UCK2 might be a potential early diagnostic and prognostic biomarker for lung cancer. Abstract : Uridine‐cytidine kinase 2 ( UCK2 ) might be a potential early diagnostic biomarker for lung cancer. UCK2 was closely related to poor progression and prognosis for lung cancer. UCK2 might be a potential prognostic biomarker for lung cancer. Tumor‐associated biological processes and signaling pathways were enriched in the UCK2 overexpression group, which indicated that UCK2 might play a vital role in lung cancer and be a potential therapeutic target for lung cancer.